Lithium-doped silicon-carbon composite material, preparation method and application
By doping metal lithium in porous carbon and deposition of nanosilicon, and performing carbon coating twice, the problem of low conductivity of the negative electrode material of lithium-ion battery is solved, the rate performance and first-time efficiency are improved, and the full-electric expansion rate is reduced.
Patent Information
- Application Number
- CN202411850424.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-04
AI Technical Summary
The conductivity of the negative electrode materials of existing lithium-ion batteries is low, resulting in a slight difference in rate performance and high-temperature storage, and the first-time efficiency and full-electric expansion rate are also low.
The conductivity and structural stability of the material are improved by doping metal lithium in porous carbon and depositing nanosilicon on its surface, followed by two carbon coatings through passivation gas and carbon source gas.
It significantly improves the rate performance and first-time efficiency of lithium-ion batteries, reduces the full-electric expansion rate, and improves high-temperature storage performance.
Smart Images

Figure CN119560548A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of negative electrode materials for lithium-ion batteries, and in particular to a lithium-doped silicon-carbon composite material, a preparation method and an application thereof. Background Art
[0002] With the continuous advancement of science and technology, people have put forward higher requirements on the capacity and energy density of batteries, which requires the search for better negative electrode materials.
[0003] Compared with traditional carbon negative electrode materials, silicon as a negative electrode material has the following advantages:
[0004] 1. Large capacity: The theoretical specific capacity of silicon can reach 4200mAh / g, which is about 10 times that of carbon. Therefore, batteries made of silicon can store more electrical energy in the same volume, improving the working time and performance of the battery.
[0005] 2. High energy density Compared with traditional materials, such as lithium cobalt oxide and ternary materials, silicon materials have higher energy density and can achieve longer battery life.
[0006] Mainstream silicon negative electrodes can be divided into two categories: silicon-oxygen negative electrodes and silicon-carbon negative electrodes. The main advantages of silicon-oxygen negative electrodes are high reversible capacity, cycle performance and rate performance; at the same time, they have been developed for a long time and have a relatively stable process route. Its main problem is that the first coulombic efficiency is too low. The silicon-carbon negative electrode has a higher gram capacity and a higher efficiency in the first charge and discharge; however, the coulombic efficiency and cycle efficiency of its electrode are still lower than those of carbon negative electrode materials. The main common defect of silicon negative electrodes is that the expansion rate is much greater than that of carbon negative electrodes. This is caused by defects in the silicon-containing crystal structure during the lithium insertion-loss process, which is an important reason why silicon negative electrodes must be mixed and doped with carbon negative electrodes or pre-treated.
[0007] The silane cracking method is the second-generation method for preparing silicon-carbon negative electrodes. It is prepared by attaching nano-silicon to the pores of porous carbon through high-temperature pyrolysis and completing the coating.
[0008] Compared with the traditional silicon carbon prepared by sand grinding, the new silicon-carbon material prepared by silane cracking method is used in high energy density lithium-ion batteries and other fields due to its high specific capacity, low expansion and good cycle performance. However, since the raw materials for the preparation of the new silicon-carbon material are composed of porous carbon and its silane, and the porous carbon itself has poor electronic conductivity and many porous structure defects in the inner core, the rate performance of the material deviates and the high-temperature storage is slightly poor. Summary of the invention
[0009] An object of the present invention is to provide a lithium-doped silicon-carbon composite material with high electrical conductivity; another object of the present invention is to provide a method for preparing a lithium-doped silicon-carbon composite material with high electrical conductivity; a further object of the present invention is to provide a lithium-ion battery with high initial efficiency and low full-charge expansion rate.
[0010] The present invention discloses a method for preparing a lithium-doped silicon-carbon composite material, comprising the following steps:
[0011] S1: dissolving metallic lithium in an organic solvent, then mixing evenly with an amino resin and an organic lithium salt, spray drying, and introducing carbon dioxide for pre-oxidation treatment; after the pre-oxidation is completed, carbonizing and cooling in a protective gas atmosphere to obtain lithium-doped porous carbon;
[0012] S2: deposit nano-silicon on the surface and in the pores of the lithium-doped porous carbon obtained in step S1 by vapor deposition to obtain an intermediate; adopt plasma technology and introduce passivation gas to passivate the intermediate under the conditions of vacuum degree of 1-10pa, temperature of 300-600°C, and output power of 500-1000W; raise the temperature to 700-1000°C, introduce carbon source gas to carbon-coat the passivated intermediate, and cool it to room temperature to obtain a lithium-doped silicon-carbon composite material.
[0013] The preparation method disclosed in the present invention dopes metallic lithium into porous carbon, and then deposits nano-silicon in the pores and surface of the porous carbon by vapor deposition to improve the electrical conductivity of the porous carbon; and then carbon-coates the surface of the porous carbon twice by passivation treatment and carbon source gas to reduce the surface defects of the silicon-carbon material and improve the initial efficiency and rate performance.
[0014] Furthermore, in step S1, the organic solvent is a mixed organic solvent formed by biphenyl and tetrahydrofuran, dimethyltetrahydrofuran or ethylene glycol dimethyl ether, wherein the molar ratio of biphenyl to tetrahydrofuran, dimethyltetrahydrofuran or ethylene glycol dimethyl ether is 0.05-0.1:1.
[0015] Metallic lithium can be dissolved in a mixed organic solvent formed by biphenyl and tetrahydrofuran, dimethyltetrahydrofuran or ethylene glycol dimethyl ether to form a lithium solution. Doping in the form of a solution can achieve a more uniform doping effect.
[0016] Furthermore, in step S1, the amino resin is selected from one of urea-formaldehyde resin, melamine formaldehyde resin, and polyamide polyamine epoxy resin; the organic lithium salt is selected from one of lithium oxalate, lithium formate, lithium citrate, and lithium malate; and the mass ratio of the metallic lithium, the organic solvent, the amino resin, and the organic lithium salt is 1-5:500-1000:200:0.5-2.
[0017] Organic lithium salts are carbonized to form lithium-doped amorphous carbon. Since the SEI film is formed during the lithium ion charging and discharging process to consume lithium ions, the lithium-doped amorphous carbon supplements the lithium ions and improves the initial efficiency. At the same time, the organic lithium salts are carbonized to form a porous structure, which provides space for the deposition of nano-silicon and reduces expansion.
[0018] Furthermore, in step S1, the temperature of the pre-oxidation treatment is 200-300° C., and the pre-oxidation treatment time is 1-6 hours; the temperature of the carbonization treatment is 800-1200° C., and the carbonization treatment time is 1-6 hours.
[0019] Furthermore, in step S2, the operation process of vapor deposition of nano-silicon is: evacuating to a pressure of ≤0.01Mpa, heating to 400-600°C, and introducing silane gas.
[0020] Furthermore, in step S2, the flow rate of the introduced silane gas is 10-100 mL / min, and the introduction time is 30-300 min.
[0021] Furthermore, in step S2, the passivation gas is selected from one of CO, CS2, CCl4, C2Cl4, and CCl2Br2; the flow rate of the passivation gas is 10-100 mL / min, and the time is 60-300 min.
[0022] Nano-silicon deposited by silane gas decomposition is too active and easily burns, posing a safety hazard. The surface of nano-silicon is carbon-coated and passivated using a plasma method to reduce its activity.
[0023] Furthermore, in step S2, the carbon source gas is selected from one of methane, ethane, ethylene and acetylene, and the flow rate of the carbon source gas is 10-100 mL / min, and the time is 60-300 min.
[0024] The surface of the material is passivated through plasma technology to form a thin and dense passivation layer for easy transportation; then carbon coating is carried out through conventional vapor deposition method to form a double-layer carbon coating. The carbon layer obtained by passivation treatment has a high density, which can restrain the expansion of nano-silicon during charging and discharging. The outer layer of amorphous carbon isolates nano-silicon from contact with the outside air and its electrolyte, reducing its side reactions.
[0025] The present invention also discloses a lithium-doped silicon-carbon composite material, which is prepared by the preparation method described above, and the powder resistivity of the lithium-doped silicon-carbon composite material is less than 1.92Ω·cm.
[0026] The present invention also discloses a lithium-ion battery, characterized in that it includes a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, the negative electrode sheet includes the lithium-doped silicon-carbon composite material described above, the initial efficiency of the lithium-ion battery is greater than 90%, and the full-charge expansion rate is less than 65%.
[0027] The lithium-doped silicon-carbon composite material disclosed in the present invention reduces the resistivity of the composite material by doping metallic lithium into porous carbon and depositing nano-silicon on the surface of the porous carbon, thereby improving the rate performance of the lithium-ion battery; and then achieves double carbon coating on the surface of the nano-silicon by passivation gas and carbon source gas, thereby reducing the defects on the surface of the nano-silicon and avoiding direct contact between the nano-silicon and the electrolyte, thereby reducing the side reactions at the negative electrode interface of the lithium-ion battery, reducing the decomposition of the electrolyte, reducing the gas production and improving the initial efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a SEM image of the lithium-doped silicon-carbon composite material prepared in Example 1. DETAILED DESCRIPTION
[0029] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0030] Example 1
[0031] The preparation steps of lithium-doped silicon-carbon composite materials are as follows:
[0032] Step S1: 3 g of metallic lithium is dissolved in 800 g of an organic solvent (the molar ratio of biphenyl to dimethyltetrahydrofuran is 0.065:1) and dispersed evenly, and then 200 g of urea-formaldehyde resin and 1 g of lithium oxalate are added and dispersed evenly, and spray dried. The obtained powder is heated to 250° C., and carbon dioxide is introduced and kept warm for 3 hours for pre-oxidation treatment. The material obtained after pre-oxidation is placed in a tubular furnace, and the temperature is raised to 900° C. in an argon protective atmosphere for carbonization treatment for 3 hours, and then cooled to room temperature in an argon atmosphere to obtain lithium-doped porous carbon.
[0033] Step S2: transfer the lithium-doped porous carbon to a tube furnace, evacuate to a pressure of ≤0.01 MPa, and heat to 500° C., introduce monosilane gas (flow rate 50 mL / min, time 150 min), and deposit nano-silicon in the pores and surface of the porous carbon to obtain an intermediate material;
[0034] Plasma technology is used, and carbon monoxide gas is introduced. At a vacuum degree of 5 Pa, a temperature of 450° C., an output power of 800 W, a gas flow rate of 500 mL / min, and an introduction time of 300 min, the intermediate material is passivated to obtain a silicon-carbon precursor material.
[0035] The silicon-carbon precursor material was transferred to a tube furnace and heated to 850°C. Ethylene gas (flow rate 50 mL / min, time 150 min) was introduced to perform a second carbon coating on the silicon-carbon precursor material. The material was cooled to room temperature to obtain a lithium-doped silicon-carbon composite material.
[0036] Example 2
[0037] The preparation steps of lithium-doped silicon-carbon composite materials are as follows:
[0038] Step S1: dissolve 1g of metallic lithium in 500g of an organic solvent (the molar ratio of biphenyl to ethylene glycol dimethyl ether is 0.075:1) and disperse evenly, then add 200g of melamine formaldehyde resin and 0.5g of lithium formate and disperse evenly, spray dry, heat the obtained powder to 200°C, introduce carbon dioxide gas and keep it warm for 6h for pre-oxidation treatment, then place the material obtained after pre-oxidation in a tubular furnace, heat it to 800°C in an argon protective atmosphere for carbonization treatment for 6h, and cool it down to room temperature in an argon atmosphere to obtain lithium-doped porous carbon.
[0039] Step S2: transfer the lithium-doped porous carbon to a tube furnace, evacuate to a pressure of ≤0.01 MPa, heat to 400° C., introduce disilane gas (flow rate 10 mL / min, time 300 min), deposit nano-silicon in the pores and surface of the porous carbon, and obtain an intermediate material;
[0040] Plasma technology is used, and CCl4 gas is introduced, at a vacuum degree of 1 Pa, a temperature of 300 ° C, an output power of 500 W, a gas flow rate of 100 mL / min, and an introduction time of 600 min, to perform a first passivation treatment on the intermediate material to obtain a silicon-carbon precursor material;
[0041] The silicon-carbon precursor material was transferred to a tube furnace and heated to 700°C. Acetylene gas was introduced at a gas flow rate of 10 mL / min for 300 min. The silicon-carbon precursor material was carbon-coated for a second time and cooled to room temperature to obtain a lithium-doped silicon-carbon composite material.
[0042] Example 3
[0043] The preparation steps of lithium-doped silicon-carbon composite materials are as follows:
[0044] Step S1: dissolve 5 g of metallic lithium in 1000 g of an organic solvent (the molar ratio of biphenyl to ethylene glycol dimethyl ether is 0.075:1) and disperse evenly, then add 200 g of polyamide polyamine epoxy resin and 2 g of lithium citrate and disperse evenly, spray dry, heat the obtained powder to 300 ° C, introduce carbon dioxide gas and keep it warm for 1 hour for pre-oxidation treatment, then place the material obtained after pre-oxidation in a tubular furnace, heat it to 1200 ° C in an argon protective atmosphere for carbonization treatment for 1 hour, and cool it down to room temperature in an argon atmosphere to obtain lithium-doped porous carbon.
[0045] Step S2: transfer the lithium-doped porous carbon to a tube furnace, evacuate to a pressure of ≤0.01 MPa, heat to 600° C., introduce disilane gas (flow rate 100 mL / min, time 30 min), deposit nano-silicon in the pores and surface of the porous carbon, and obtain an intermediate material;
[0046] Plasma technology is used, and CCl2Br2 passivation gas is introduced. At a vacuum degree of 10 Pa, a temperature of 600° C., an output power of 1000 W, a gas flow rate of 1000 mL / min, and an introduction time of 60 min, the intermediate material is subjected to a first passivation treatment to obtain a silicon-carbon precursor material.
[0047] The silicon-carbon precursor material was transferred to a tube furnace, heated to 1000°C, and methane gas was introduced at a gas flow rate of 100 mL / min for 30 min. The silicon-carbon precursor material was carbon-coated for the second time and cooled to room temperature to obtain a lithium-doped silicon-carbon composite material.
[0048] Comparative Example 1
[0049] The difference from Example 1 is that no metallic lithium is added, and the other steps are the same as Example 1.
[0050] Comparative Example 2
[0051] The difference from Example 1 is that lithium oxalate is not added, and the rest is the same as Example 1.
[0052] Comparative Example 3
[0053] The difference from Example 1 is that the plasma method is not adopted and the carbon monoxide passivation gas is not introduced. The other steps are the same as Example 1.
[0054] Performance Testing
[0055] 1. SEM scanning electron microscope test:
[0056] The lithium-doped silicon-carbon composite material prepared in Example 1 was subjected to scanning electron microscopy testing, and the obtained SEM image is as follows Figure 1 As shown by Figure 1 It can be seen that the lithium-doped silicon-carbon composite material prepared in Example 1 presents a granular structure with a particle size between 5 and 10 μm, and the rough small particles on the surface of the material are deposited amorphous carbon.
[0057] 2. Physical and chemical tests and button battery tests:
[0058] According to the method in the national standard GB / T 38823-2020 "Silicon Carbon", the specific surface area, tap density, and carbon content of the silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-3 were respectively measured, and the resistivity of each silicon-carbon composite material was tested using a four-probe tester; the test results are shown in Table 1 below.
[0059] The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-3 were used as active materials for negative electrode plates of batteries and were respectively prepared and assembled into 10 button batteries.
[0060] Among them, the specific preparation process of each button battery is as follows:
[0061] Preparation of battery negative electrode sheets: Add a binder, a conductive agent and a solvent to the silicon-carbon composite materials (as the active material of the battery negative electrode sheets) corresponding to Examples 1-3 and Comparative Examples 1-3, stir to make slurry, coat on copper foil, dry and roll to obtain each battery negative electrode sheet; wherein, the binder is LA132 binder, the conductive agent is SP (conductive carbon black), and the solvent is NMP, and the ratio is: silicon-carbon composite material: SP: LA132: NMP = 95g: 1g: 4g: 220mL.
[0062] Preparation of button cells: LiPF6 solution was used as the electrolyte, wherein the concentration of LiPF6 was 1 mol / L, and the solvent used was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) in a weight ratio of 1:1; a metal lithium sheet was used as the counter electrode, and a polypropylene (PP) film was used as the diaphragm. The simulated battery was assembled in an argon-filled glove box, and the electrochemical performance was performed on a Wuhan Blue Electric CT2001A battery tester. The test conditions were: the charge and discharge voltage range was 0.005V to 2.0V, and the charge and discharge rate was 0.1C; a full-charge expansion test was also performed: the thickness D1 of the negative electrode sheet of the button cell after rolling was tested, and then the negative electrode sheet of the button cell was dissected when it was fully charged to 100% SOC, and the thickness D2 of the negative electrode sheet was tested, and then the full-charge expansion rate = (D2-D1) / D1*100% was calculated; the test results are shown in Table 1 below.
[0063] Table 1 Test results
[0064] First discharge specific capacity (mAh / g) First efficiency (%) Carbon content <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Tap density (g / cm 3 ).]]> Powder resistivity (Ω·cm) Fully charged expansion Silicon grain size (nm) Example 1 1838.6 91.7 48.2% 5.9 1.02 1.45 59.9% 1.5 Example 2 1881.7 91.9 47.9% 7.1 1.05 1.92 64.3% 1.9 Example 3 1811.4 90.9 48.6% 6.3 0.97 1.11 57.8% 1.4 Comparative Example 1 1764.5 88.3 49.9% 4.5 0.90 4.93 82.0% 2.3 Comparative Example 2 1812.5 87.5 50.6% 4.2 0.86 3.05 77.3% 2.1 Comparative Example 3 1801.5 87.9 50.1% 4.3 0.88 3.58 80.1% 2.2
[0065] It can be seen from Table 1 that the button cells made using the silicon-carbon composite materials provided in Examples 1-3 are significantly better than those in Comparative Examples 1-3 in terms of first discharge specific capacity and first efficiency; the reason may be that the silicon-carbon composite materials prepared in Examples 1-3 use lithium-doped porous carbon to improve the ionic and electronic conductivity of the material, thereby reducing the powder resistivity of the material, reducing the polarization of the material, and improving the specific capacity of the material; at the same time, lithium doping of the material improves the first efficiency of the material.
[0066] 3. Soft pack battery test:
[0067] The silicon-carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-3 were doped with 90% artificial graphite as negative electrode materials (i.e., negative electrode plates), and the ternary material LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 is used as the positive electrode material, the electrolyte and the diaphragm to assemble a 5Ah soft-pack battery; the diaphragm of the soft-pack battery is Celegard 2400, the electrolyte is LiPF6 solution, the solvent of the LiPF6 solution is a mixed solution of EC and DEC with a volume ratio of 1:1, and the concentration of LiPF6 is 1.3mol / L; the following performance tests are carried out on each soft-pack battery:
[0068] a. Liquid absorption capacity test: Use a 1mL burette and absorb VmL of electrolyte, add a drop on the surface of the negative electrode, and time it until the electrolyte is completely absorbed. Record the time t and calculate the liquid absorption rate V / t of the negative electrode. The test results are shown in Table 2.
[0069] b. Liquid retention rate test: Calculate the theoretical liquid absorption of the negative electrode according to the electrode parameters mL, and weigh the weight of the negative electrode m2. Soak the negative electrode in the electrolyte for 24 hours, weigh the weight of the negative electrode m3, calculate the liquid absorption of the negative electrode m3-m2, and calculate according to the following formula:
[0070] Liquid retention rate = (m3-m2)*100% / mL; the test results are shown in Table 2 below.
[0071] Table 2. Liquid absorption capacity test results
[0072] Liquid suction speed (S) Fluid retention rate Example 1 34 91.4% Example 2 26 90.1% Example 3 42 89.9% Comparative Example 1 76 85.9% Comparative Example 2 89 84.7% Comparative Example 3 81 85.3%
[0073] It can be seen from Table 2 that the liquid absorption and liquid retention capabilities of the silicon-carbon composite materials prepared in Examples 1-3 are significantly higher than those of Comparative Examples 1-3. Therefore, the silicon-carbon composite materials prepared in Examples 1-3 have better wettability to the electrolyte. The reason is that the silicon-carbon composite materials prepared in Examples 1-3 have a high specific surface area.
[0074] c. Rate and cycle performance: Cycle performance test and rate test were performed on each soft pack battery, where the test conditions for the cycle performance test were: charge and discharge voltage range 2.5-4.2V, temperature 25±3.0℃, charge and discharge rate 1.0C / 1.0C, and cycle number 500 times; the cycle performance test results are detailed in Table 3. The test conditions for the rate test were: test the capacity retention rate under the charge rate (0.2C / 0.5C / 1C / 2C / 3C); the test results are shown in Table 4 below.
[0075] Table 3. Cyclic performance test results
[0076] Silicon-carbon composite materials for lithium-ion batteries Initial capacity retention rate (%) Capacity retention after 500 cycles (%) Example 1 100 93.1 Example 2 100 92.2 Example 3 100 91.8 Comparative Example 1 100 85.9 Comparative Example 2 100 83.6 Comparative Example 3 100 86.7
[0077] It can be seen from Table 3 that the cycle performance of the silicon-carbon composite materials prepared in Examples 1-3 is significantly better than that of the composite materials in Comparative Examples 1-3. The reason is that the silicon-carbon composite materials prepared by the method of the present invention have lower expansion and smaller silicon reduction, which reduces the expansion of the battery during its cycle and improves the cycle performance.
[0078] Table 4. Rate test results
[0079] 0.2C 0.5C 1C 2C 3C Example 1 100% 98.3% 97.2% 95.4% 91.6% Example 2 100% 99.1% 97.5% 95.8% 92.1% Example 3 100% 98.2% 97.1% 95.0% 91.2% Comparative Example 1 100% 95.2% 94.1% 92.2% 88.5% Comparative Example 2 100% 96.0% 94.5% 92.6% 88.8% Comparative Example 3 100% 96.7% 95.1% 93.2% 89.4%
[0080] It can be seen from Table 4 above that the soft-pack lithium-ion batteries prepared using the silicon-carbon composite materials provided in Examples 1-3 have better rate performance than those of Comparative Examples 1-3. The main reason for this may be that the lithium-doped silicon-carbon composite materials provided by the present invention have high powder conductivity and large specific surface area, thereby improving the rate performance of the material.
[0081] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a lithium-doped silicon-carbon composite material, characterized in that: The steps include: S1: dissolving metallic lithium in an organic solvent, then mixing evenly with an amino resin and an organic lithium salt, spray drying, and introducing carbon dioxide for pre-oxidation treatment; after the pre-oxidation is completed, carbonizing and cooling in a protective gas atmosphere to obtain lithium-doped porous carbon; S2: deposit nano-silicon on the surface and in the pores of the lithium-doped porous carbon obtained in step S1 by vapor deposition to obtain an intermediate; adopt plasma technology and introduce passivation gas to passivate the intermediate under the conditions of vacuum degree of 1-10pa, temperature of 300-600°C, and output power of 500-1000W; raise the temperature to 700-1000°C, introduce carbon source gas to carbon-coat the passivated intermediate, and cool it to room temperature to obtain a lithium-doped silicon-carbon composite material.
2. The method for preparing a lithium-doped silicon-carbon composite material according to claim 1, characterized in that: In the step S1, the organic solvent is a mixed organic solvent formed by biphenyl and tetrahydrofuran, dimethyltetrahydrofuran or ethylene glycol dimethyl ether.
3. The method for preparing a lithium-doped silicon-carbon composite material according to claim 1, characterized in that: In the step S1, the amino resin is selected from one of urea-formaldehyde resin, melamine formaldehyde resin, and polyamide polyamine epoxy resin; the organic lithium salt is selected from one of lithium oxalate, lithium formate, lithium citrate, and lithium malate; and the mass ratio of the metallic lithium, the organic solvent, the amino resin, and the organic lithium salt is 1-5:500-1000:200:0.5-2.
4. The method for preparing a lithium-doped silicon-carbon composite material according to claim 1, characterized in that: In the step S1, the temperature of the pre-oxidation treatment is 200-300° C., and the pre-oxidation treatment time is 1-6 hours; the temperature of the carbonization treatment is 800-1200° C., and the carbonization treatment time is 1-6 hours.
5. The method for preparing a lithium-doped silicon-carbon composite material according to claim 1, characterized in that: In step S2, the operation process of vapor deposition of nano-silicon is as follows: evacuating to a pressure of ≤0.01 MPa, heating to 400-600° C., and introducing silane gas.
6. The method for preparing a lithium-doped silicon-carbon composite material according to claim 5, characterized in that: In the step S2, the flow rate of the introduced silane gas is 10-100 mL / min, and the introduction time is 30-300 min.
7. The method for preparing a lithium-doped silicon-carbon composite material according to claim 1, characterized in that: In step S2, the passivation gas is selected from one of CO, CS2, CCl4, C2Cl4, and CCl2Br2; the flow rate of the passivation gas is 10-100 mL / min, and the time is 60-300 min.
8. The method for preparing a lithium-doped silicon-carbon composite material according to claim 1, characterized in that: In the step S2, the carbon source gas is selected from one of methane, ethane, ethylene and acetylene, and the flow rate of the carbon source gas is 10-100 mL / min, and the time is 60-300 min.
9. A lithium-doped silicon-carbon composite material, characterized in that: The lithium-doped silicon-carbon composite material is prepared by the preparation method according to any one of claims 1 to 8, and the powder resistivity of the lithium-doped silicon-carbon composite material is less than 1.92Ω·cm.
10. A lithium ion battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet comprises the lithium-doped silicon-carbon composite material as claimed in claim 9, and the initial efficiency of the lithium-ion battery is greater than 90%, and the full-charge expansion rate is less than 65%.
Citation Information
Cited By
High-power silicon-carbon composite material, preparation method and application thereof
CN121076099A
Solid electrolyte doped silicon-carbon composite material, preparation method and application thereof
CN121076100A